2005
DOI: 10.1186/1472-6920-5-34
|View full text |Cite
|
Sign up to set email alerts
|

Doctor-patient interaction in Finnish primary health care as perceived by first year medical students

Abstract: BackgroundIn Finland, public health care is the responsibility of primary health care centres, which render a wide range of community level preventive, curative and rehabilitative medical care. Since 1990's, medical studies have involved early familiarization of medical students with general practice from the beginning of the studies, as this pre-clinical familiarisation helps medical students understand patients as human beings, recognise the importance of the doctor-patient relationship and identify practici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 9 publications
1
23
0
6
Order By: Relevance
“…This should be taken into consideration in interpreting the data collected. However, general practices are extensively involved in early patient contact (36). In Dornan et al's systematic review, primary care settings were reported as the settings most often used (6).…”
Section: Discussionmentioning
confidence: 99%
“…This should be taken into consideration in interpreting the data collected. However, general practices are extensively involved in early patient contact (36). In Dornan et al's systematic review, primary care settings were reported as the settings most often used (6).…”
Section: Discussionmentioning
confidence: 99%
“…15 Further, computer use often caused physicians to lose rapport with their patients. 15,16,18,19 It has been proposed that physicians' behavioral style, computer and communication skills, as well as their experience, affect patient-doctor communication in the context of EMR use. 20,21 In order to understand better the effects of computerized information systems on patient safety and quality of care, it is important to comprehend how physicians actually use them.…”
Section: Introductionmentioning
confidence: 99%
“…A familiarização dos estudantes com a prática geral melhora consideravelmente as habilidades de comunicação e compreensão de percepções dos pacientes, ajuda os pacientes a entender alunos como seres humanos e ajuda a reconhecer a importância da relação médico-paciente 8 .…”
Section: Categoria 1 Formação Profissional No Susunclassified